PERBANDINGAN PENGARUH PENDEKATAN PROBLEM-BASED LEARNING DAN PENDEKATAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DAN MOTIVASI BELAJAR SISWA - Rosmala, Amelia; Panjaitan, Regina Lichteria; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
This research aims to compare problem-based learning approach and guided inquiry approach that has a greater influence on mathematics communication ability and students’ learning motivation. This research used quasi experimental research method with the nonequivqlent control group design. The population of this research is all fourth grade students in the elementary school of Lelea subdistrict who use school based curriculum (KTSP). The sample in this research is taken fourth grade students of SDN Tugu II and fourth grade students of SDN Pengauban I. The instrument used in this research is test of mathematics communication ability and attitude scale test of learning motivation, teacher performance observation and students’ activity and interview. Based on the value of significance and the mean of final value, it is concluded that the PBL has a better effect than the guided inquiry approach to students' mathematics communication ability. However the students of PBL class, guided inquiry students have equal learning motivation in mathematics.Therefore, there is no positive and significant correlation between mathematics communication ability with students’ learning motivation.